947 The 'silent video' as a training aid for emergency department major incident management. Issue 3 (21st February 2022) - Paranamana, Supathum; Roland, Damian; Coats, Tim
Abstract : Aims/Objectives/Background: There is a specific need to refresh knowledge of and update Major Incident Protocols (MIP) but a department may have less than one Major Incident (MI) every 5 years. As part of our department's COVID-19 pandemic response, a 'silent movie' of PPE donning-and-doffing techniques was played on large screens in the background during clinical handovers. We theorised that this technique might be effective in training ED staff on the MIP. Methods/Design: We created a seven-minute silent video about our MIP using volunteer actors from ED Doctors, Nurses, and Ancillary Healthcare Staff. Brief captions describing key aspects of the MIP were overlaid on video clips and images. The video was played on a continuous loop on wall mounted TVs for six continuous weeks, located within the handover room used by all ED staff members. A questionnaire was sent out to all staff in ED to assess how the video's content improved understanding of the MIP. The design of the questionnaire was based on the Moore's Expanded Education Outcome Model. Results/Conclusions: 64 of the respondents viewed the video. From the cohort, 70% were satisfied with the format of the video and 84% believed the content to be useful. Using the Moore's outcome model there was an increase in 62.1% of the declarative knowledge post viewing, and a 47.8% increase in the confidence of knowing what to do in a MI. The confidence in being able to locate the MIP tray and perform well in a MI had also increased by 47.2% and 42.02% respectively. The repeated silent video format was an effective teaching tool, as reflected in all aspects of Moore's model; majority of respondents showed improved confidence in all aspects of the MIP. Background training videos could form part of ED training, especially for topics which are not included in formal training programs.